Contraceptive experience and perception, a survey among Ukrainian women - Volodymyr Podolskyi; Kristina Gemzell-Danielsson; Lena Marions (BMC, 2018)
Abstract Background Abortion rate in Ukraine is high and the use of effective contraceptive methods is low. Aiming to explore women's knowledge and attitudes towards modern contraceptive methods, we performed a survey among women with a recent pregnancy. Methods A convenience sample of 500 women who had an abortion or a delivery (250 women post abortion and 250 women post partum) in Kiev, Ukraine was chosen to participate in the study. A self-administered questionnaire which included questions regarding demographics, plans for future pregnancy, and contraceptive usage, knowledge and the main barriers to contraceptive uptake was distributed. Results Most women in our study expressed a wish to postpone or refrain from future pregnancies after the current abortion or delivery. The experience of and the knowledge regarding long acting contraception (LARC) such as intrauterine contraception (IUC) and implants were however low. Barrier methods and oral contraceptives were the most commonly used methods while only a few women had used IUC. Conclusion Since most of the respondents did not want a pregnancy in the near future, the findings from this study thus indicate a low uptake for effective and acceptable contraceptive methods and especially LARC methods. Increasing the availability of LARC methods as well as adequate and updated information from providers are essential to reduce the rate of unplanned pregnancy and abortion among Ukrainian women.